Political orientation and COVID-19 policy preferences during the early pandemic: a comparative analysis of China and South Korea - Zhou Fang (Frontiers in Public Health, 2025)
BackgroundThe COVID-19 pandemic posed an unprecedented challenge to governments and societies worldwide, highlighting the complex relationship between state policies and public acceptance during crises. This study examines how regime types, political tendencies, and social culture influence citizen’s preferences for epidemic prevention policies in China and South Korea.Materials and methodsA cross-sectional online survey was operated in May 2020 to citizens aged ≥ 20 years in China and South Korea. Using the stratified quota sampling method, This study collected 2,254 valid responses from China and 1,783 from South Korea. Moderated mediation effect analysis were conducted to explore the factors shaping public attitudes toward epidemic control measures.ResultsThere are clear differences in policy preferences between the two countries. Chinese citizens were more likely to support strict, government-led measures, while South Korean respondents showed lower levels of support. Political tendency was the strongest predictor of policy preferences in both countries, with those favoring greater government authority more likely to support strict epidemic control measures. While government satisfaction significantly influenced policy acceptance in China, its impact was minimal in South Korea. Additionally, collectivism moderated the relationship between political tendency and policy preferences. In highly collectivist environments, social norms reinforced support for control measures, while in more individualist contexts, personal political beliefs had a stronger influence on policy acceptance.ConclusionThis study provides important evidence that citizen preferences for epidemic prevention are shaped by complex interaction between political institutions, cultural values, and individual beliefs. These findings can inform more effective communication strategies and policy design when governments prepare for future pandemic.